2021
DOI: 10.3390/cancers13133305
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-DOTATOC-PET/MRI—A Secure One-Stop Shop Imaging Tool for Robotic Radiosurgery Treatment Planning in Patients with Optic Nerve Sheath Meningioma

Abstract: Optic nerve sheath meningiomas (ONSM) are rare but can lead to irreversible blindness. Hybrid imaging may enhance tumor delineation and diagnostic accuracy via receptor binding. However, relevant clinical data for ONSM are lacking. We evaluated the feasibility of receptor-based hybrid imaging prior to robotic radiosurgery (RRS). We retrospectively analyzed all of our institution’s patients with suspected ONSM who underwent combined positron emission tomography and magnetic resonance imaging (PET/MRI) with gall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…The initial search yielded 1606 published articles (PubMed: 803; Scopus: 673; Web of Science: 107; Cochrane: 23). A total of 63 studies were included with the a priori criteria: 25 were case reports and 38 were case series, categorized with levels of evidence IV and V, respectively [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The initial search yielded 1606 published articles (PubMed: 803; Scopus: 673; Web of Science: 107; Cochrane: 23). A total of 63 studies were included with the a priori criteria: 25 were case reports and 38 were case series, categorized with levels of evidence IV and V, respectively [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ,…”
Section: Resultsmentioning
confidence: 99%
“…DOTATOC (78.2%) was utilized more frequently than DOTATATE (21.8%), and Pelak et al [ 69 ] also reported the use of DOTANOC in 19 patients. [ 68 Ga]Ga-DOTA-SSTR PET studies were mostly fused with CT/MRI studies and implemented to improve volume contouring for radiation planning, such as stereotactic radiotherapy (SRT) [ 20 , 26 , 28 , 33 ], intensity-modulated radiotherapy (IMRT) [ 27 , 29 ], conventional radiotherapy [ 46 , 49 , 51 , 66 ], cyber knife radiosurgery (CKRS) [ 17 , 18 ], and carbon/proton therapy [ 32 , 69 ]. The implementation of [ 68 Ga]Ga-DOTA-SSTR PET proved to significantly improve target definition in meningiomas of the skull base, parafalcine, intraosseous, or affecting the optic nerve sheath, also favoring reduced radiation doses to adjacent organs at risk.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PET with SSTR ligands is particularly useful in cases of ambiguous, non-contributive MRI and for specific regions which are known to be difficult to appreciate by MRI, such as the base of the skull and bony structures. The rare but aggressive optic nerve sheath meningioma entity almost invariably takes up SSTR ligands [ 59 ]. PET with SSTR ligands is thus better suited than contrast-enhanced MRI to delineate tumor margins, which is potentially informative for tumor resection.…”
Section: Current Uses Of Pet Imaging In Brain Tumorsmentioning
confidence: 99%